EFEKTIVITAS MODEL PEMBELAJARAN AUDITORY INTELLECTUALY REPETITION (AIR) DENGAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI SMK KESEHATAN SIDIMPUAN HUSADA - Irna Purwati Simamora (JURNAL MathEdu (Mathematic Education Journal), 2019)
abstract The aims of this study is to describe the effectiveness of using Auditory Intellectually Repetition (AIR) learning model students’ mathematical problem solving ability at the tenth grade students of SMK Kesehatan Sidimpuan Husada. This research was conducted by applying experimental method with 24 students as the sample and they were taken by using total sample technique. Test and observation were used in collecting the data. Based on descriptive analysis, it was found (a) the average of students’ mathematical problem solving ability before using AIR learning model was 44.39 (fair category) and after using AIR learning model was 82.95 (very good category) and (b) 29.2% students got effective category, 62.5% students got effective category, and 8.3% students got enough effective category. Keywords: AIR learning model, problem solving ability